(3TQM cGajI GHf GdMGLHs - (3eMeO Hf GdMSf GdQVj GdCSJQGHGPj , fLe GdOjf,J (B686 (3g` s ((3GdegOi Hf Ydi Hf CMeO Hf eMeO GdgGOi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi LdJ BdGDg Yf Cf JMGW HYO , hJYGdJ cHQjGDg Yf Cf JTed HMO s
(3BNQgG (B:s
(3dCf gPg GdgGA JQGO EPG de jbUO Gdhba , hGddg CYde HGdUhGH Je GdcJGH s
(3GdLRA GdChd GdPi jfJgi HGdhQbI (B112 (3H cJH SfI (B901 (3g`s
(3hYdi GdLRA GdChd bQGAI hSeGY hebGHdI SfI (B911 (3g`s
(3hJeJ cJGHI GdLRA GdKGfi SfI(B909(3g`s
(3HJQbje GdUaMGJ EVWQGH s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
Keywords: (3GdfMhs